Penyelesaian Sengketa Pengadaan Tanah Pada Pembangunan New Yogyakarta International Airport Berdasarkan Undang-Undang tentang Pengadaan Tanah Bagi Pembangunan Untuk Kepentingan Umum - Millati Hanifah Wardani; Andi Salman Maggalatung (Faculty of Sharia and Law State Islamic University Syarif Hidayatullah Jakarta, 2022)
Resolving land acquisition disputes for the public interest, it is fitting for the state to pay attention to values outside of the rule of law itself, including the value of social justice and the value of benefits to guarantee the basic rights of affected communities. This study aims to find out provisions for land acquisition for development in the public interest and implementation of Law Number 2 of 2012 concerning Land Procurement in the construction of New Yogyakarta International Airport. The process of land acquisition for development in the public interest is carried out in the stages of planning, preparation, implementation, and submission of results. The implementation of land acquisition is intended as an instrument for infrastructure development programs for community welfare as mandated by Law Number 2 of 2012 concerning Land Procurement for Development in the Public Interest.